2010
DOI: 10.1631/jzus.b1000051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of differently polarized microwave radiation on the microscopic structure of the nuclei in human fibroblasts

Abstract: Abstract:To investigate the influence of microwave radiation on the human fibroblast nuclei, the effects of three variants of electromagnetic wave polarization, linear and left-handed and right-handed elliptically polarized, were examined. Experimental conditions were: frequency (f) 36.65 GHz, power density (P) at the surface of exposed object 1, 10, 30, and 100 µW/cm 2 , exposure time 10 s. Human fibroblasts growing in a monolayer on a cover slide were exposed to microwave electromagnetic radiation. The layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…The effect increased with intensity. Right-handed polarization induced a stronger effect than left-handed 41 . These experiments show that not only linear but circular and elliptical polarizations are important parameters for the biological action of EMR, and that molecular structure of biomolecules may be important for the interaction between polarized EMF and the biological tissue.…”
Section: Discussionmentioning
confidence: 80%
“…The effect increased with intensity. Right-handed polarization induced a stronger effect than left-handed 41 . These experiments show that not only linear but circular and elliptical polarizations are important parameters for the biological action of EMR, and that molecular structure of biomolecules may be important for the interaction between polarized EMF and the biological tissue.…”
Section: Discussionmentioning
confidence: 80%
“…However, a number of outliers appear with higher d values. These are older studies (Garaj-Vrhovac et al, 1991;Zotti-Martelli et al, 2000;Kesari and Behari, 2009;Shckorbatov et al, 2010;Karaca et al, 2012). Their results are not consistent with subsequent studies on similar endpoints and may be in error.…”
Section: Effect Sizesmentioning
confidence: 66%
“…Two of the studies also examined telomere length and found no statistically significant difference between exposed and unexposed cells [15,19]. Last, a Ukrainian research group examined different skin cell types in three studies and reported an increase in chromosome condensation in the nucleus [20][21][22]; these results have not been independently verified. Overall, there was no confirmed evidence of MMWs causing genotoxic damage in epithelial and skin cells.…”
Section: Genotoxicitymentioning
confidence: 99%